Street Smart Intelligence Preparation of the Battlefield for Urban Operations - Medby, Jamison Jo (RAND Corporation, 2002)
Intelligence preparation of the battlefield (IPB), the Army's traditional methodology for finding and analyzing relevant information for its operations, is not effective for tackling the operational and intelligence challenges of urban operations. The authors suggest new ways to categorize the complex terrain, infrastructure, and populations of urban environments and incorporate this information into Army planning and decisionmaking processes.